2019
DOI: 10.15666/aeer/1701_199211
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Temperature Conditions on Yield and Physiological Properties of Rice (Oryza Sativa L.)

Abstract: Temperature is one of the major factors which have a significant effect on plants. This study was carried out to investigate the effect of temperature variation on physio-biochemical characteristics of two rice cultivars i.e., Basmati385 and Xiangyaxiangzhan. A pot experiment with three different treatments of day-night temperature dynamics was carried out in a randomized complete block design with three replications. Treatments included T1: 33 °C/27 °C, T2: 27 °C/21 °C, T3: 21/15 °C under 1200X yellow light i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 30 publications
(31 reference statements)
1
5
0
Order By: Relevance
“…Because of under those stresses, the proline in fragrant rice was primarily synthesized by the glutamic acid pathway. This idea about NT condition causing stress is supported by the lower activities of SOD, POD, and CAT and the higher content of MDA in the no-tillage treatment compared to the rotary tillage treatment in present study because MDA production in an important indicator of oxidative stress and SOD could dismutase superoxide radical whereas POD and CAT could scavenge H 2 O 2 [21, 35]. Furthermore, the decreased grain yield and nitrogen accumulation also indicated that fragrant rice under the no-tillage condition experienced decreased growth and development compared to that under CK and PT conditions.…”
Section: Discussionmentioning
confidence: 53%
“…Because of under those stresses, the proline in fragrant rice was primarily synthesized by the glutamic acid pathway. This idea about NT condition causing stress is supported by the lower activities of SOD, POD, and CAT and the higher content of MDA in the no-tillage treatment compared to the rotary tillage treatment in present study because MDA production in an important indicator of oxidative stress and SOD could dismutase superoxide radical whereas POD and CAT could scavenge H 2 O 2 [21, 35]. Furthermore, the decreased grain yield and nitrogen accumulation also indicated that fragrant rice under the no-tillage condition experienced decreased growth and development compared to that under CK and PT conditions.…”
Section: Discussionmentioning
confidence: 53%
“…Yuxiangyouzhan, the super rice, is not sensitive to low temperatures during the seedling stage and has high seed yields, as well as other positive attributes 59,60 . Xiangyaxiangzhan, a non-super rice, can withstand increased temperatures (21/15 °C, 27/21 °C, 33 °C/27 °C), and its photosynthesis and synthesis of photosynthetic pigments are enhanced 61 ; this cultivar is sensitive to low temperatures and has a low survival rate 62 . Moreover, Yuxiangyouzhan has a higher heat resistance than does Xiangyaxiangzhan 63 .…”
Section: Methodsmentioning
confidence: 99%
“…A stronger antioxidant system in rice ensures stable rice production stabilization. Furthermore, chlorophyll biosynthesis and gas exchange for photosynthesis are affected by the environment [20,24] while higher antioxidant enzyme activity can better maintain the stability of cells and ensure the progress of various physiological activities [25,26]. Therefore, we deduced that the application of La might protect chlorophyll biosynthesis in aromatic rice by increasing the activities of antioxidant enzymes and that this would enhance photosynthesis and dry matter accumulation and finally increase grain yield.…”
Section: Discussionmentioning
confidence: 99%
“…At the tillering stage (20 days after transplanting), booting stage (40 days after transplanting), heading stage (60 days after transplanting), grain-filling stage (75 days after transplanting) and maturity stage (90 days after transplanting, also 1 day before harvesting) in the second and third experiments, the net photosynthetic rate was determined with the portable photosynthesis system (LI-6400, LI-COR, USA) according to the method described by Luo et al (2019). At the same time, a 'SPAD-502' SPAD meter (Konica Minolta, Japan) was used to perform a precise, rapid and nondestructive estimation of the leaf chlorophyll contents.…”
Section: Determination Of Net Photosynthetic Rate Chlorophyll Content and Dry Matter Accumulationmentioning
confidence: 99%